2013
DOI: 10.1142/s0218625x13500492
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION AND HARDNESS OFCoPCOATINGS OBTAINED FROM DIRECT CURRENT ELECTRODEPOSITION USING GLUCONATE BATH

Abstract: Direct current electrodeposition of Co – P alloy coatings were carried out using gluconate bath and they were characterized by employing techniques like XRD, FESEM, DSC and XPS. Broad XRD lines demonstrate the amorphous nature of Co – P coatings. Spherical and rough nodules are observed on the surface of coatings as seen from FESEM images. Three exothermic peaks around 290, 342 and 390°C in DSC profiles of Co – P coatings could be attributed to the crystallization and formation of Co 2 P phase in the coatings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In both PC and DC Co–W–P coatings, it is seen that the two exothermic peaks approach each other at higher phosphorous content in the deposit. Similar effect has also been reported by our group for Co–P coatings obtained from gluconate bath . A tendency toward the formation of single crystalline peak is found with increasing P content.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In both PC and DC Co–W–P coatings, it is seen that the two exothermic peaks approach each other at higher phosphorous content in the deposit. Similar effect has also been reported by our group for Co–P coatings obtained from gluconate bath . A tendency toward the formation of single crystalline peak is found with increasing P content.…”
Section: Resultsmentioning
confidence: 97%
“…Weston et al have used gluconate bath for the electrodeposition of wear and corrosion resistant Co–W alloys and established a relationship between the bath composition and the alloy properties . Recently, Bera and coworkers have demonstrated the codepositon of P and W with Co and Ni from gluconate bath and performed detailed characterization and extensive electronic structure analysis by X‐ray photoelectron spectroscopy (XPS) . It has also been found that Co–W coatings possess GFA which has been confirmed by detailed DSC and heat treatment analysis .…”
Section: Introductionmentioning
confidence: 88%
“…When the temperature was up to 340 • C, Co 2 P compounds were formed, and the microhardness increased once again. Both processes could increase the microhardness of the coatings [16]. Consequently, the microhardness of Co-P coatings increased after the heat treatment.…”
Section: Effect Of the Heat Treatment Temperature On Microhardness Ofmentioning
confidence: 97%
“…Kosta [11,14] found that the grain size of the Co-P coatings deposited under single pulse current was obviously smaller than that deposited under direct current. They also concluded that the corrosion resistance of the Co-P alloy layer was better than that of the hard chrome layer from the potentiodynamic polarization curve, however, the corrosion resistance degraded severely after annealing at 400 • C. Some works [1,9,15,16] suggest that heat treatment could improve the microhardness of the Co-P alloy. After heat treatment for 10 min at 400 • C, the microhardness of the Co-P alloy could rise to 1000-1100 HV, while the hardness of hard chromium was usually 900-1000 HV.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-crystalline Co-P coatings are relatively new alloy films, which are often applied via electrodeposition ( as well as electroless deposition techniques (Ref [15][16][17][18]. High current efficiency, the possibility to obtain thick coatings with no voids and microcracks, fewer significant environmental impacts, high hardness and wear resistance, proper ductility and thermal stability, noticeable corrosion resistance, and ability to improve properties by heat treatment, all have made nano-crystalline Co-P electrodeposits suitable substitute for the hard chromium coatings ( Ref 2,3,5,15,19). Therefore, Co-P coatings have recently been used on the inner sides of turbine shafts, and gears (Ref 2, 3).…”
Section: Introductionmentioning
confidence: 99%